Can an Outdoor Learning Environment Improve Children's Academic Attainment? A Quasi-Experimental Mixed Methods Study in Bangladesh. Issue 10 (December 2020) - Khan, Matluba; McGeown, Sarah; Bell, Simon
The present study adopted a quasi-experimental mixed method approach to investigate the influence of an improved school ground on children's academic performance. In total, 123 children from two (intervention and control) primary schools in Bangladesh participated. In the intervention school, a barren school ground was redesigned with several behavior settings (e.g., gardens and amphitheater) for teaching and learning. Treatment group children ( n = 29) received math and science classes outdoors, while a comparison group ( n = 32) received usual indoor classes. A control school with no changes to the outdoor environment was included ( n = 62). The redesigned school ground was associated with higher levels of academic attainment. Furthermore, all intervention schoolchildren perceived more opportunities to explore in the redesigned school ground. Qualitative insights suggest the diverse settings provided more opportunities to explore, experiment, and work collaboratively. These results highlight the potential for school ground design to contribute to improvement of children's academic attainment in developing countries.